Spatial localization of genes determined by intranuclear DNA fragmentation with the fusion proteins lamin KRED and histone KRED und visible light - Waldeck, Waldemar; Mueller, Gabriele; Glatting, Karl-Heinz; Hotz-Wagenblatt, Agnes; Diessl, Nicolle; Chotewutmonti, Sasithorn; Langowski, Jörg; Semmler, Wolfhard; Wießler, Manfred; Braun, Klaus (International journal of medical sciences, 2013)
The highly organized DNA architecture inside of the nuclei of cells is accepted in the scientific world. In the human genome about 3 billion nucleotides are organized as chromatin in the cell nucleus. In general, they are involved in gene regulation and transcription by histone modification. Small chromosomes are localized in a central nuclear position whereas the large chromosomes are peripherally positioned. In our experiments we inserted fusion proteins consisting of a component of the nuclear lamina (lamin B1) and also histone H2A, both combined with the light inducible fluorescence protein KillerRed (KRED). After activation, KRED generates reactive oxygen species (ROS) producing toxic effects and may cause cell death. We analyzed the spatial damage distribution in the chromatin after illumination of the cells with visible light. The extent of DNA damage was strongly dependent on its localization inside of nuclei. The ROS activity allowed to gain information about the location of genes and their functions via sequencing and data base analysis of the double strand breaks of the isolated DNA. A connection between the damaged gene sequences and some diseases was found.